Iridium oxide nanoribbons with metastable monoclinic phase for highly efficient electrocatalytic oxygen evolution - Liao, Fan; Yin, Kui; Ji, Yujin; Zhu, Wenxiang; Fan, Zhenglong; Li, Youyong; Zhong, Jun; Shao, Mingwang; Kang, Zhenhui; Shao, Qi (Nature communications, 2023)
Metastable metal oxides with ribbon morphologies have promising applications for energy conversion catalysis, however they are largely restricted by their limited synthesis methods. In this study, a monoclinic phase iridium oxide nanoribbon with a space group of C2/m is successfully obtained, which is distinct from rutile iridium oxide with a stable tetragonal phase (P42/mnm). A molten-alkali mechanochemical method provides a unique strategy for achieving this layered nanoribbon structure via a conversion from a monoclinic phase K 0.25 IrO 2 (I2/m (12)) precursor. The formation mechanism of IrO 2 nanoribbon is clearly revealed, with its further conversion to IrO 2 nanosheet with a trigonal phase. When applied as an electrocatalyst for the oxygen evolution reaction in acidic condition, the intrinsic catalytic activity of IrO 2 nanoribbon is higher than that of tetragonal phase IrO 2 due to the low d band centre of Ir in this special monoclinic phase structure, as confirmed by density functional theory calculations. Well-defined metastable phase nanostructures are a core issue for catalyst design. Here, the authors report metastable monoclinic phase IrO2 nanoribbons obtained via a molten-alkali mechanochemical method, which exhibit intrinsic high performance towards the acidic oxygen evolution reaction.